More than illustrated music aesthetics of hybrid media between pop, art and video - Dreckmann, Kathrin 1982-; Vomberg, Elfi 1986- (Bloomsbury Academic, 2023)
"Examines the processes of hybridization between music video, film, and video art by presenting current theoretical discourses and exploring crucial questions of art practice"--
Keywords: Intermedialität; Ästhetik; Musikvideo; Videokunst; Film; Music videos; Art and music; Aufsatzsammlung